PENINGKATAN HASIL BELAJAR IPA SISWA DENGAN MENGGUNAKAN METODE EKSPERIMEN DI SD - Nurti, Syafni (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
Under field conditions, the results of science learning in class V SDN 20 Muaro Sijunjung low, this is because teachers rarely conduct experiments to find the concept and still use the old way or conventional. For that researchers using eksperimen methods. This study is an action research using qualitative and quantitave approaches. The results obtained from studying the cognitive aspects of cycle I and II  cycle 68.95, 86.35, affective aspect cycle I gained 68 and 82.5 second cycle and psychomotor aspects gained 72.85 cycle I and cycle II acquired 84.31. Thus, this study has been successful in improving student learning outcomes   Kata Kunci: hasil belajar, pembelajaran IPA dan metode eksperimen.